Correlating dough elastic recovery during sheeting to flour analyses and rheological properties - Ren, Danqiu (Kansas State University, 2007)
In commercial bakeries, the baker expects to get the same bread loaf, including weight and size, after sheeting the same size dough piece. Doughs made from different flours have different elastic recoveries to a great extent, which has an effect on the dough’s size and density. Products made from differently elastic doughs can’t have the same shape and height. Weight may also be affected. The dough rheological behaviors of five flours and their blends having different chemical and physical properties were measured as were changes in thickness and snapback (thickness of the machined dough sheet relative to the roll gap) immediately following sheeting. Dough snapback was determined to be a function of both processing parameters, reduction ratio, and dough rest time, as well as different flour properties. The predication equation for dough snapback is based on multiple flour properties and sheeting conditions. Among the variables, Mixograph work, reduction ratio, and dough rest time were the main factors affecting the elastic characteristics of the doughs. Minimum snapback occurred with the weakest flour experiencing the longest rest time and the smallest reduction ratio. A 7-factor equation was found to be robust to predict the snapback of several flours, by combining Mixograph work, reduction ratio, dough rest time, Mixograph peak height and mixing time, Alveograph P/L, and protein content.
Keywords: Dough; rheological properties; sheeting; elasticity; snapback; Agriculture, Food Science and Technology (0359)